Algorithms for the remote sensing of the Baltic ecosystem (DESAMBEM). Part 2: Empirical validation - Darecki, M; Ficek, D; Krezel, A; Ostrowska, M; Majchrowski, R; Wozniak, S B; Bradtke, K; Dera, J; Wozniak, B (Oceanologia, 2008)
This paper is the second of two articles on the methodology of the remote sensing of the Baltic ecosystem. In Part 1 the set of DESAMBEM algorithms for determining the major parameters of this ecosystem on the basis of satellite data and in details the mathematical apparatus of these algorithms were presented. The effects of the practical application of the algorithms and their validation, the latter based on satellite maps of selected Baltic ecosystem parameters are presented (Part 2). These parameters are: the distributions of the sea surface temperature (SST), the Photosynthetically Available Radiation (PAR) at the sea surface, the surface concentrations of chlorophyll a and the total primary production of organic matter. Particular emphasis was laid on analysing the precision of estimates of these and other parameters of the Baltic ecosystem, determined by remote sensing methods. The errors in these estimates turned out to be relatively small; hence, the set of DESAMBEM algorithms should in the future be utilised as the foundation for the effective satellite monitoring of the state and functioning of the Baltic ecosystem.